Nothing is Impossible: Effects of Anxiety on Academic Procrastination - Natalya, Lina (Faculty of Psychology, Universitas Surabaya, 2013)
The aim of this study was to find out whether anxiety caused by tasks affect college student procrastination behavior, while applying the Temporal Motivation Theory (TMT) (Steel, 2007). A non-randomized pretest-posttest control group design was conducted with subjects who were every college student of the even semester of the 2011/2012 generation who were taking the Measurement Instrument Construction subject. In order to measure the procrastination levels, this study used Pure Procrastination Scale (PPS) and the time to hand-in the tasks, while in order to measure the anxiety levels, this study used a scale consisting of 22 items. Research results showed that there was a correlation between anxiety and academic procrastination (r = .417; p = .000). The experiment group revealed that subjects with high anxiety levels chose to immediately work on a task, while subjects with high anxiety levels in the control group chose to procrastinate. Tujuan studi ini adalah untuk mengetahui apakah kecemasan yang ditimbulkan oleh tugas berpengaruh pada perilaku prokrastinasi mahasiswa tersebut dengan menggunakan Temporal Motivation Theory (TMT) (Steel, 2007). Suatu desain kelompok kontrol pretes-pasca-tes dikenakan pada semua mahasiswa yang sedang mengambil mata kuliah Penyusunan Alat Ukur pada semester genap tahun ajaran 2011/2012. Penelitian ini menggunakan Pure Procrastination Scale (PPS) dan jam pengumpulan tugas untuk mengukur tingkat prokrastinasinya, sedangkan untuk kecemasan digunakan skala yang terdiri atas 22 butir pernyataan. Hasil studi ini menunjukkan bahwa ada hubungan antara kecemasan dan prokrastinasi akademik (r = .417 ; p = .000). Pada kelompok eksperimen seseorang yang cemas lebih memilih untuk segera mengerjakan tugasnya, sedangkan pada kelompok kontrol terbukti seseorang yang cemas lebih memilih untuk melakukan penundaan.